The Sinclairs, a family of dinosaurs (Journal of Parents and Teachers, 2025)
The article refers to the Sinclairs, an American middle-class family living without renouncing their dinosaur feelings, during the post-volcanic Age, where the writers recreate these times and turn them into a parody of modern civilization.
Keywords: parody